Beneficial effects of retroreflective materials in urban canyons: results from seasonal monitoring campaign. (October 2015) - Rossi, F; Morini, E; Castellani, B; Nicolini, A; Bonamente, E; Anderini, E; Cotana, F
Abstract: Urban Heat Island (UHI) is a phenomenon that happens in urban areas consisting in higher temperatures than those in the surrounding rural areas. Cool materials and urban forestry have been identified as the mean countermeasures to this phenomenon. The specific research target was to investigate the benefit that can be obtained by the application of new retro-reflective (RR) cool materials on building envelopes in urban canyons. An ideal RR is a high reflective material that reflect incident radiation backward to the same direction of incidence. The test facility is made of two twin arrays resembling urban canyons with different aspect ratios. On the East array a cool, white, diffusive material is applied. On the West array a cool, white Retro-Reflective (RR) material is applied. The result of a seasonal (summer) monitoring campaign is discussed, with a particular focus on the temperature trends inside canyons with the same geometry but different envelope materials. While temperatures measured by the vertical sensors reveal a higher surface temperature of the RR, air temperatures and pavements' superficial temperatures are lower when RR are applied. These results suggest that RR materials have a cooling potential as coatings in urban canyons, and can thus improve urban climate conditions during summer.